If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + -3)(x + -3) + 3 = 13 Reorder the terms: 2(-3 + x)(x + -3) + 3 = 13 Reorder the terms: 2(-3 + x)(-3 + x) + 3 = 13 Multiply (-3 + x) * (-3 + x) 2(-3(-3 + x) + x(-3 + x)) + 3 = 13 2((-3 * -3 + x * -3) + x(-3 + x)) + 3 = 13 2((9 + -3x) + x(-3 + x)) + 3 = 13 2(9 + -3x + (-3 * x + x * x)) + 3 = 13 2(9 + -3x + (-3x + x2)) + 3 = 13 Combine like terms: -3x + -3x = -6x 2(9 + -6x + x2) + 3 = 13 (9 * 2 + -6x * 2 + x2 * 2) + 3 = 13 (18 + -12x + 2x2) + 3 = 13 Reorder the terms: 18 + 3 + -12x + 2x2 = 13 Combine like terms: 18 + 3 = 21 21 + -12x + 2x2 = 13 Solving 21 + -12x + 2x2 = 13 Solving for variable 'x'. Reorder the terms: 21 + -13 + -12x + 2x2 = 13 + -13 Combine like terms: 21 + -13 = 8 8 + -12x + 2x2 = 13 + -13 Combine like terms: 13 + -13 = 0 8 + -12x + 2x2 = 0 Factor out the Greatest Common Factor (GCF), '2'. 2(4 + -6x + x2) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(4 + -6x + x2)' equal to zero and attempt to solve: Simplifying 4 + -6x + x2 = 0 Solving 4 + -6x + x2 = 0 Begin completing the square. Move the constant term to the right: Add '-4' to each side of the equation. 4 + -6x + -4 + x2 = 0 + -4 Reorder the terms: 4 + -4 + -6x + x2 = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -6x + x2 = 0 + -4 -6x + x2 = 0 + -4 Combine like terms: 0 + -4 = -4 -6x + x2 = -4 The x term is -6x. Take half its coefficient (-3). Square it (9) and add it to both sides. Add '9' to each side of the equation. -6x + 9 + x2 = -4 + 9 Reorder the terms: 9 + -6x + x2 = -4 + 9 Combine like terms: -4 + 9 = 5 9 + -6x + x2 = 5 Factor a perfect square on the left side: (x + -3)(x + -3) = 5 Calculate the square root of the right side: 2.236067978 Break this problem into two subproblems by setting (x + -3) equal to 2.236067978 and -2.236067978.Subproblem 1
x + -3 = 2.236067978 Simplifying x + -3 = 2.236067978 Reorder the terms: -3 + x = 2.236067978 Solving -3 + x = 2.236067978 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + x = 2.236067978 + 3 Combine like terms: -3 + 3 = 0 0 + x = 2.236067978 + 3 x = 2.236067978 + 3 Combine like terms: 2.236067978 + 3 = 5.236067978 x = 5.236067978 Simplifying x = 5.236067978Subproblem 2
x + -3 = -2.236067978 Simplifying x + -3 = -2.236067978 Reorder the terms: -3 + x = -2.236067978 Solving -3 + x = -2.236067978 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + x = -2.236067978 + 3 Combine like terms: -3 + 3 = 0 0 + x = -2.236067978 + 3 x = -2.236067978 + 3 Combine like terms: -2.236067978 + 3 = 0.763932022 x = 0.763932022 Simplifying x = 0.763932022Solution
The solution to the problem is based on the solutions from the subproblems. x = {5.236067978, 0.763932022}Solution
x = {5.236067978, 0.763932022}
| 2(x-3)+3=13 | | x^4-x^3-2x^2+4x-24=0 | | (X^2+24)= | | 3x^2-11x-3=-x^2 | | Un=5+(0.1n-0.1) | | Un=5+(0.1n+0.1) | | Cos(5x)-cos(9x)=0 | | z^2-(3-2i)z+(5-5i)=0 | | 6x=n+4 | | 4x^2+12x+9=49x | | 4x^3+12x+9=49x | | -6.8(7.9+1.2*-7.3)+3.7=4.2*-7.3+40.90016 | | 1/8+2/3= | | 1/3+2/3= | | 5y+11=6 | | -6.8(7.9+1.2x)+3.7=4.2x+40.90016 | | x^2-1x+40=0 | | (m+2n+1)(m-n+2)=5 | | x^2+12x+35x=0 | | 4x+13=-29-2 | | x+2x+6x+18x=160 | | 7(x*5)=9(6+4) | | 4m^2+4x=60 | | 3(2p-1)=8 | | -4x^2+24x-63=0 | | -2x^2-10x+14=0 | | 3(4x-7)=-33 | | 2xsquare+15y-13=0 | | -x^2-7= | | (-5)-(-11)=x | | (-5)-(-11)= | | 9xsquared=324 |